Women and poverty in 21st century America - Dail, Paula W. (McFarland, 2012)
"This volume offers a feminist perspective on the 21st century war on poverty, illustrated by the words of women forced to live every day with social policies. Topics include the struggles of daily life, crime, health care, education, employment, and a discussion of capitalism, inequality, greed, and moral obligation in a free society"--Provided by publisher.